EDUCATIONAL REFORM IN THE EU COUNTRIES AND UKRAINE: HISTORICAL BACKGROUND, CURRENT ISSUES AND FUTURE PROSPECTS - Dzhurylo, Alina (Studies in Comparative Education, 2018)
The article deals with the historical background, current issues and future challenges of educational reform in the countries of the European Union. It has been shown that the educational policy of the last century was aimed at increasing the length of compulsory secondary education to 18 years, early engagement of children in primary education and increasing its duration. The issue of decentralization as an educational trend in all European countries since the 1920s has been raised. The author analyses educational policy of the EU at the present stage, which is aimed at forming in European schools the necessary skills for their successful self-realization in society, including digital skills for future jobs, and the overcoming of gender differences in mathematics and sciences starting from school level. In the EU's current educational policy the following priority areas can be identified: all pupils should gain the competences they need; every pupil should benefit from high-quality learning, including migrant children; early childhood education and care should be more widely available, support for learners with special needs must be improved within mainstream schooling and reduction of early school leaving; teachers, school leaders, and educators should receive more support, including career-long professional learning opportunities; quality assurance should be further developed to ensure a more effective, equitable and efficient governance of school education and to facilitate learner mobility. The issue concerning creating a European education area by 2025 is revealed. The European vector of Ukraine’s development has been analysed, which has been considered as a priority since the proclamation of independence and confirmation of the Association Agreement between Ukraine and the European Union.